Avian Influenza (H9N2) Outbreak In Iraq - Khamas, Emad J. (The Iraqi Journal of Veterinary Medicine, 2008)
An outbreak of avian influenza (AI) (H9N2) occurred in broiler, layers andbreeder chicken farms in Iraq during 2004-2007. Mortality between 30% and70% in broilers and 5% and 10% in layers and breeders were commonlyobserved on the affected farms. Mixed infections of the influenza virus withother respiratory pathogens particularly Newcastle Disease (ND) virus andInfectious Bronchitis (IB) virus were thought to be responsible for such highmortality. ELISA test was used to detect ND, AI and IB antibodies. Clinicalsigns included , decrease feed consumption, swelling of the face and typicalsevere respiratory signs. Gross lesions included extensive hyperemia of therespiratory system, cheesy exudates in the tracheal bifurcation extending into thesecondary bronchi, hyperemia and hemorrhagic ulcers in the proventriculus andintestine.